Hydrothermal activities contribute to the strong metal enrichments during early Cambrian: evidence from the comparison between black rock series in Tarim and South China - Wang, Hongzuo; Sun, Yonglong; Wang, Dan; Shu, Xujie; Cheng, Cheng; Qian, Peng (Frontiers in Earth Science, 2024)
The early Cambrian period is a critical time in Earth's history, marked by the second oxygenation of the atmosphere (known as the Neoproterozoic Oxidation Event) and the rapid evolution of animals, as well as the worldwide large-scale deposits. Polymetallic Ni-Mo deposits have been previously reported in the black rocks at the base of the Cambrian strata on the Yangtze Block, South China, while their genesis is still controversial, and their global occurrences are uncertain. Therefore, we conduct a comprehensive analysis of trace elements and rare earth elements in the black rocks at the base of the Yurtus Formation in the Sugaitblak section (SGT) in Aksu, Tarim Block, and then make a comprehensive study by combining our and other data from the Tarim and Yangtze Block. The distribution patterns of the trace and rare earth element data from our study and another two sections in the Aksu area have shown that the black rocks in the Tarim were strongly enriched in V, Sr, Mo, Ba, and U, moderately enriched in Zn, Cu, Cr, and Pb, and slightly depleted in Ni, and Co during the early Cambrian. These enriched elements could mainly originate from the waning hydrothermal fluids, and then precipitate and preserve in sediments under anoxic environment. The comparison of trace elements in the black rocks between the Tarim and the Yangtze Block suggests that the types of enriched metal elements in these two regions were different, and metal concentrations in the Yangtze Block were much higher than those in the Tarim by 1-3 orders of magnitude. This result indicates that there are no polymetallic Ni-Mo enrichment layers in the black rocks in the Tarim during the early Cambrian, and the widespread polymetallic Ni-Mo enrichments in South China have been more likely influenced by the local hydrothermal activity. It could be further speculated that the early Cambrian period may have been an active period for seafloor hydrothermal activity, with locally different chemical components in hydrothermal fluids. Abundant metal nutrients brought by these hydrothermal activities may have been a potential factor for the rapid evolution of life during this period.